EFEKTIVITAS REFORMASI BIROKRASI TERHADAP PENCAPAIAN TUJUAN ORGANISASI : (Studi Kasus Pada BPS Provinsi Kalimantan Utara Tahun 2022) - Lambertha Gundalibra sari (Jurnal Administrasi Publik, 2023)
The government a public service organization certainly has an obligation to provide excellent service to all people. Excellent service often becomes polemic where people are dissatisfied with the services provided by the government because the service quality is lowand not on time. One of the methods by BPS of West Kalimantan Province is to carry out bureaucratic reform with the aim of knowing whether or not bureaucratic reform is effective in achieving organizational goals. This study used descriptive qualitative method. The data will then analyzed in depth using analysis by conducting an analysis based on the interpretation of primary secondary data. The results of the research show that bureaucratic reform BPS North Kalimantan Province still not optimal because there are still many employees who neglect their duties and responsibilities. In addition, BPS North Kalimantan Province needs to innovate to improve employee performance so that organizational goals can be achieved.